Injection Safety: Knowledge and Practices among Nursing Personnel in Tertiary Care Teaching Hospital of Marathwada Region of Maharashtra, India - Kulkarni, Rohini S; Giri, Purushottam A (Archives of Community Medicine and Public Health, 2016)
Background: Unsafe injection practices put patients and healthcare providers at risk of infectious and non-infectious adverse events, sound knowledge and skillful practices of nurses are vital to breaks the chain of blood borne diseases transmission caused by unsafe injection practices. Objectives: To assess the knowledge and practices amongst nurses regarding injection safety in tertiary care teaching Hospital of Marathwada Region of Maharashtra, India. Methods: A cross section study was carried out from April to May 2016 in tertiary care teaching hospital of Marathwada region of Maharashtra, India. A total of 70 nurses were enrolled in this study. A pre-designed questionnaire which assessed knowledge and practices regarding injection safety tool was used to collect data. Results were analyzed using frequency, means, and percentage whenever appropriate. Results:In this study, majority 82.86% were females and 52.86% had less than 5 years working experience, and 91.4% of the respondents had good knowledge of HIV, hepatitis B and C transmission through unsafe injection. Majority 92.85% nurses knew that sharp waste should be discarded in blue container but while practicing only 40% of nurse’s segregate sharp waste and 81.43% of the nurses didn’t wear protective gloves while giving injection. Conclusion: The present study concluded that there was average level of knowledge and poor practices on injection safety amongst nurses; therefore there is need for regular training session and close supervision of the nurses. These will greatly enhance the knowledge and practice of injection safety among nurses.